Lending and Borrowing in the Teaching of Sirach (Sir 29:1–7) - Piwowar, Andrzej (Verbum Vitae, 2023)
Among the various topics and issues that Ben Sira discusses in his book is the issue of borrowing. The sage covers it in detail and at length in Sir 29:1–7, presenting it not from a financial and economic perspective, but from a sapiential viewpoint, appropriate to the nature of his work. The purpose of this article is to explore Sirach’s teaching on the subject of borrowing and lending of material goods. As a preliminary matter, the issue of borrowing in the setting of the ancient Near East and in biblical Israel is presented in a highly synthetic manner. Next, the boundaries of the literary unit that is the subject of the presented analyses and its structure are defined. In the remainder of the article, the Greek text of Sir 29:1–7 (the Hebrew version of this pericope is not known) is exegetically analyzed drawing on the historical-critical method. The examined literary unit is divided into two main parts. The first is a discussion of the general rules concerning lending and borrowing, i.e. based on the texts of the Torah, the obligation to grant a loan also reminds one of the obligation to return the debt according to the terms agreed upon. The second part of the pericope depicts the difficulties associated with not returning borrowed goods on the part of dishonest borrowers (delay in returning the loan, making excuses, even aggression towards the creditor). Fundamental to the sage’s teaching on the subject of borrowing are the texts of the Pentateuch saying that one should give loans. However, the author is a realist and therefore devotes much of his reflection on the issue to the difficulties involved in returning borrowed goods, with a view to encouraging his disciples to adopt an attitude of prudence and caution lest they suffer the loss of some of their possessions. Yet, despite these risks, he encourages them to support those in need with loans.